Lessons from building and using EUROMOD - Christine Lietz; Daniela Mantovani (University of Essex, Institute for Social and Economic Research (ISER), 2006)
By the mid 1990s the potential and usefulness of microsimulation models for researching tax benefit systems had found widespread acceptance. Nevertheless models were not widely available for independent or academic research in all countries of the European Union (EU). Even more important, carrying out consistent comparative tax-benefit microsimulation analysis was still an apparently impossible task. The time seemed ready for a European-Union-wide tax-benefit microsimulation model. This paper is devoted to explaining the reasons for building EUROMOD, its added value compared to existing models, the trade-offs faced by its builders and lessons that have been learnt from developing such an integrated model. Moreover, it aims to provide an insight into the wide range of possible applications of EUROMOD, underlined by summarising some indicative findings of studies, which have used the model.
Keywords: C8; I3; 330; European Union; Microsimulation; Model Building